Genetic Evidence for O-Specific Antigen as Receptor of Pseudomonas aeruginosa Phage K8 and Its Genomic Analysis - Pan, Xuewei; Cui, Xiaoli; Zhang, Fenjiao; He, Yang; Li, Lingyan; Yang, Hongjiang (Frontiers in Microbiology, 2016)
Phage therapy requires the comprehensive understanding of the mechanisms underlying the host-phage interactions. In this work, to identify the genes related to Pseudomonas aeruginosa phage K8 receptor synthesis, 16 phage-resistant mutants were selected from a Tn5G transposon mutant library of strain PAK. The disrupted genetic loci were identified and they were related to O-specific antigen (OSA) synthesis, including gene wbpR, ssg, wbpV, wbpO, and Y880_RS05480, which encoded a putative O-antigen polymerase Wzy. The LPS profile of the Y880_RS05480 mutant was analyzed and shown to lack the O-antigen. Therefore, the data from characterization of Y880_RS05480 by TMHMM and SDS-PAGE silver staining analysis suggest that this locus might encode Wzy. The complete phage K8 genome was characterized as 93879 bp in length and contained identical 1188-bp terminal direct repeats. Comparative genomic analysis showed that phage K8 was highly homologous to members of the genus PaP1-like phages. On the basis of our genetic findings, OSA of P. aeruginosa PAK is proven to be the receptor of phage K8. The highly conserved structural proteins among the genetic closely related phages suggest that they may recognize the same receptor.